A CASE OF ADVANCED CERVICAL PREGNANCY - Senanayake, H M; Kaluarachchi, A; Sivasuriyam, A; Randeniya, C (My University, 2012)
A 33-year old primigravida who has been married for 3 years and investigated fot subfertility was transferred from the teaching hospital - Galle at a POA of 18 weeks with mild bleeding PV. Ultrasound diagnosis of viable cervical presnancv had been made and >hc was given two doses of merhotTixate before transfer to oui unit. \\c gave two more doses of methotrixate and she aborted her babv and had a massive haemorrhage. Setting: Department of Obstetrics and Gynaecology, Faculty of Medicine, Colombo. Method: Consecutive non-pregnant normal women seeking treatment for male infertility were recruited for assessment of fasting blood glucose, C and T G concentrations. Age matched pregnant women who underwent the 75g Oral Glucose Tolerance Test (OGTT) between 20 - 24 weeks of gestation based on identified risk factors for diabetes mellitus were recruited concurrently and their fasting plasma C and T G concentrations were measured. Results: 45 consenting non-pregnant women and 95 consenting pregnant women referred for OGT T were recruited. All non-pregnant women had normal fasting blood glucose concentrations (mean 97.7 +/- 1.6 mg/dl). 50/95 pregnant women had normal OGT T and 45 had abnormal OGT T based on WH O criteria. The mean age of non- pregnant women was 33.2 +/- 2.1 and among pregnant women 30.2 +/- 1.2 (p = 0.07). Non-pregnant women had a fasting plasma C of 215 +/ -12 mg/dl and T G of 94.9 +/- 8.2. mg/dl. Pregnant women with normal OGT T vs. abnormal OGT T had fasting C 239.2 +/- 7.2 mg/dl vs. 218 +/- 17.2 mg/dl (p = 0.05); and fasting T G of201.6 +/- 8 mg/dl vs. 180.9 +/-11.3 mg/dl (p • 0.06). Anova single factor comparison of non-pregnant women and pregnant women with normal and abnormal OGT T revealed a significant elevation of fasting C andTG in normal pregnant women (p = 0.04). Conclusion: A significant elevation of fasting C and T G concentrations occur in normal pregnancy; while abnormal glucose tolerance in pregnancy does not confer an additional risk on plasma lipid concentrations.